Церковь Ованеса Мкртича Гандзасарского монастыряи ее скульптурная программа - Аветисян, Тагуи (Институт языкознания РАН)
Церковь Ованеса Мкртича (Иоанна Крестителя) Гандзасарского монастыря в Арцахе (XIII в.) своим богатым и неповторимым скульптурным убранством занимает особое место в искусстве средневековой Армении. Фасады церкви, порталы и особенно его барабан богато украшены растительным и геометрическим орнаментом, изображениями животных и птиц, а также фигурами ктиторов и библейскими сюжетами. Большая часть внешних скульптурных изображений церкви Ованеса Мкртича сконцентрирована на ее барабане, который символически ассоциируется с Горним миром и Небесным Иерусалимом, что придает особую значимость их визуальному восприятию и интерпретации. The Church of Hovhanes Mkrtich (John the Baptist) of the Gandzasar Monastery (XIII century AD) in Artsakh, with its rich and unique sculptural decoration, has a special place in the art of medieval Armenia. The facades of this church, portals, and especially its drum are richly decorated with floral and geometric ornaments, various architectural elements, images of animals and birds, as well as figures of donators and biblical scenes. Most of the external sculptural images of the church of Hovhanes Mkrtich are presented on its drum, which is symbolically associated with the Heavenly Sphere and Heavenly Jerusalem and gives special significance to their visual perceptions and interpretations. Based on previous studies, the article gives a number of its own comments and interpretations regarding the external sculptural images of the church of Hovhanes Mkrtich of the Gandzasar Monastery.
Keywords: Искусство средневековья